Manajemen humas dalam meningkatkan partisipasi masyarakat di Madrasah Aliyah Negeri 1 Merangin - Ariyani, Rika; Munip, Al; Nasril, Nasril; Hadi, Sukandar; Darni, Darni; Nurlinda, Nurlinda (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2024)
This study aims to analyze the role of public relations (PR) management in enhancing community participation at MAN 1 Merangin. The research employs a qualitative approach with a field study method. Data were collected through observation, interviews, and documentation, then analyzed using triangulation techniques. The findings of the study reveal the following: first, the planning of PR management to increase community participation at MAN 1 Merangin is carried out through PR work meetings and providing information to the community about program implementation while identifying community needs. Second, the implementation of PR activities to enhance community participation at MAN 1 Merangin is conducted through the promotion of the school via media channels. Third, PR evaluation at MAN 1 Merangin is conducted using two methods: direct evaluation and quarterly evaluations (before the odd semester, after the odd semester, and before class promotion). The evaluation covers both active and passive participation.